2018
DOI: 10.1007/s00041-018-9615-5
|View full text |Cite
|
Sign up to set email alerts
|

Bohr Sets in Triple Products of Large Sets in Amenable Groups

Abstract: We answer a question of Hegyvári and Ruzsa concerning effective estimates of the Bohr-regularity of certain triple sums of sets with positive upper Banach densities in the integers. Our proof also works for any discrete amenable group, and it does not require all addends in the triple products we consider to have positive (left) upper Banach densities; one of the addends is allowed to only have positive upper asymptotic density with respect to a (possibly very sparse) ergodic sequence. MAIN RESULTSand if S is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Much more recently, Bergelson and Ruzsa [BR09] showed that the triple sumset r•A+s•A+t•A contains a Bohr neighborhood of zero when r, s, and t are integers with r +s+t = 0 and A is a set of positive upper asymptotic density. Uniformity in the dimension and diameter of Bohr sets contained in triple sumsets was recently demonstrated in broad generality by Björklund and Griesmer [BG19].…”
Section: Introductionmentioning
confidence: 88%
“…Much more recently, Bergelson and Ruzsa [BR09] showed that the triple sumset r•A+s•A+t•A contains a Bohr neighborhood of zero when r, s, and t are integers with r +s+t = 0 and A is a set of positive upper asymptotic density. Uniformity in the dimension and diameter of Bohr sets contained in triple sumsets was recently demonstrated in broad generality by Björklund and Griesmer [BG19].…”
Section: Introductionmentioning
confidence: 88%
“…For example, in Z, the set A of odd integers has d * (A) = 1/2, and A − A + A = A, which does not contain a Bohr neighborhood of 0. Nevertheless, A − A + A contains Bohr neighborhoods of many elements of A whenever d * (A) > 0; see [19], [8].…”
Section: Bohr Neighborhoods In Iterated Difference Setsmentioning
confidence: 99%
“…Hegyvári and Ruzsa [27] generalized Bogolyubov's theorem in a different direction, showing that there exist "many" a ∈ Z for which A − A + A − a contains a Bohr set. Björklund and the first author [10,Theorem 1.1] strengthened this result by providing explicit bounds on the rank and radius of such a Bohr set, and generalized the result to all countable amenable discrete groups (and hence all countable discrete abelian groups).…”
Section: Introductionmentioning
confidence: 97%
“…It is well known that all locally compact abelian groups are amenable. Følner [14,15] generalized Theorem A to discrete abelian groups, and the results of [10] mentioned above apply to countable discrete amenable groups which are not necessarily abelian. Against this backdrop, our objective in this program is threefold.…”
Section: Introductionmentioning
confidence: 99%